2018
DOI: 10.1029/2017jd026979
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Mechanisms for MJO Decay Over the Maritime Continent

Abstract: Eastward propagating Madden‐Julian oscillation (MJO) events that develop in the Indian Ocean from November to April are separated into events whose convective anomalies do and do not propagate across the Maritime Continent (MC). Propagating (P) events are divided into strong (sP) and weak (wP) subsets based on the initial amplitudes of their convective anomalies. Eastward decaying (ED) MJO events have initial amplitudes similar to those of wP events. Roughly half of all MJO events encounter westward propagatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 49 publications
8
86
0
Order By: Relevance
“…The mean state conditions favorable for the propagation of the WPIM are strongest mainly east of the Indian Ocean, which may help explain why the WPIM weakens significantly before reaching the Indian Ocean. A preliminary analysis suggests that ENSO may play a significant role in the interannual variability of intraseasonal convective events, in agreement with DeMott et al ().…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean state conditions favorable for the propagation of the WPIM are strongest mainly east of the Indian Ocean, which may help explain why the WPIM weakens significantly before reaching the Indian Ocean. A preliminary analysis suggests that ENSO may play a significant role in the interannual variability of intraseasonal convective events, in agreement with DeMott et al ().…”
Section: Discussionmentioning
confidence: 99%
“…The spatial structures revealed in Figure resemble the salient structure of El Niño‐Southern Oscillation (ENSO) extremes, for example, with years of strong MJO propagation having a more El Niño‐like large‐scale structure and years of strong WPIM propagation having a more La Niña‐like large‐scale structure. DeMott et al () also showed that the large‐scale background state conditions for strong MJO propagating events versus MJO events terminating at the Maritime Continent have similar structures. Therefore, it is possible that the interannual variability we are detecting related to strong MJO and WPIM years is impacted by the strength of ENSO.…”
Section: Interannual Variability Over the Wpmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, stronger MJO events have higher chances to survive the barrier effect than weaker ones. But all strong MJO events do not survive the barrier effect and a few weak ones do (Chen & Wang, 2018;DeMott et al, 2018;Kim et al, 2016;Zhang & Ling, 2017). Strength of the MJO alone is neither necessary nor sufficient to overcome the barrier effect.…”
Section: 1029/2019gl081962mentioning
confidence: 99%
“…The reasons for the MC barrier effect on MJO propagation are not well understood. Proposed mechanisms for the barrier effect include reduced surface fluxes by the islands (Maloney & Sobel, 2004;Sobel et al, 2010), distorted low-level circulations by topography (Hsu & Lee, 2005;Inness & Slingo, 2006;Tan et al, 2018;Wu & Hsu, 2009), and specific large-scale patterns of moisture and circulations (DeMott et al, 2018;Feng et al, 2015;Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%